2016
DOI: 10.1523/jneurosci.0648-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Single-Neuron Sensitivity to Millisecond Variations in Temporally Patterned Communication Signals

Abstract: In many sensory pathways, central neurons serve as temporal filters for timing patterns in communication signals. However, how a population of neurons with diverse temporal filtering properties codes for natural variation in communication signals is unknown. Here we addressed this question in the weakly electric fish Brienomyrus brachyistius, which varies the time intervals between successive electric organ discharges to communicate. These fish produce an individually stereotyped signal called a scallop, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Which mechanisms contribute to setting integration timescales? Single neurons can be sensitive to spatiotemporal input sequences ( Segundo et al, 1963 ; Branco et al, 2010 ; Baker et al, 2016 ). Learning to detect a specific sequence ( Hardy and Buonomano, 2016 ) can be accomplished by spike timing-dependent plasticity ( Masquelier et al, 2008 ; Klampfl and Maass, 2013 ; Gütig, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Which mechanisms contribute to setting integration timescales? Single neurons can be sensitive to spatiotemporal input sequences ( Segundo et al, 1963 ; Branco et al, 2010 ; Baker et al, 2016 ). Learning to detect a specific sequence ( Hardy and Buonomano, 2016 ) can be accomplished by spike timing-dependent plasticity ( Masquelier et al, 2008 ; Klampfl and Maass, 2013 ; Gütig, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Which mechanisms contribute to setting integration timescales? Single neurons can be sensitive to spatiotemporal input sequences [57-59]. Learning to detect a specific sequence [60] can be accomplished by spike timing-dependent plasticity [61-63].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they suggested that, since the corollary discharge inhibition of the nELL can preserve the temporal information of communication signals from other fish, the downstream pathway should analyze temporal features of the signal. Indeed, future studies demonstrated that the ELa extracts information about temporal features of the EOD waveform that reflect the identity of signaling fish ( Friedman and Hopkins, 1998 ; Lyons-Warren et al, 2013 ), and that the posterior exterolateral nucleus (ELp), to which ELa sends its only output, extracts temporal patterns of inter-pulse intervals that reflect the behavioral state of signaling fish ( Carlson, 2009b ; Baker et al, 2016 ). Owing partly to this corollary discharge inhibition, mormyrid fishes provided a unique opportunity to study how the nervous system decodes temporal signals during communication ( Xu-Friedman and Hopkins, 1999 ; Baker et al, 2013 ).…”
Section: Corollary Discharge Inhibition For Communicationmentioning
confidence: 99%